Implementing ITIL - service support in the infrastructure and service unit of CICT, UTM - Ayat, Masarat (2008)
ITIL implementation is rapidly growing in the organizations. One of the major parts of ITIL framework is service support which is including of several processes especially Configuration Management, Helpdesk Management and so on. In addition, there are several ITIL-based frameworks such as Microsoft Operation Framework (MOF) that they are trying to show some guidelines to implement those best practices processes too. Centre Information Communication Technology (CICT) is the heart of UTM in terms of information technology and related platforms. Infrastructure and Service Department is one of the suborganizations of this centre that it is includes four different units with their specific tasks. The aim of this research is to provide a framework to guide this department to document and standardize department's activities based on ITIL best practices. The proposed ITIL framework will try to improve the quality of services at Infrastructure and Service Department of UTM. The proposed framework includes KPI, Steps, Scope of work and other related information to prepare guideline to implement ITIL-Service Support at Infrastructure and Service Department of UTM. In order to achieve to this objective the needed information gathered from several resources such as interview, observation, questionnaire and available documents. Moreover, this research includes a tool to automate these ITIL-service support activities that calls ADU@ITIL system.